2015
DOI: 10.1038/srep18499
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule compound IMB-LA inhibits HIV-1 infection by preventing viral Vpu from antagonizing the host restriction factor BST-2

Abstract: Human BST-2 inhibits HIV-1 replication by tethering nascent virions to the cell surface. HIV-1 codes Vpu that counteracts BST-2 by down-regulating this restriction factor from the cell surface. This important function makes Vpu a potential therapeutic target. Yet, no agents have been reported to block Vpu from antagonizing BST-2. In this study, we report a small molecule compound IMB-LA that abrogates the function of Vpu and thereby strongly suppresses HIV-1 replication by sensitizing the virus to BST-2 restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
(84 reference statements)
1
12
0
Order By: Relevance
“…New treatments designed to disrupt the function of Nef and Vpu will likely aid host immunity combat HIV-1 infection by restoring normal PM physiology. In fact, Nef and Vpu antagonists are currently in development [ 176 , 177 ]. Given the ability of Nef and Vpu to overcome intrinsic restriction factors and innate immunity, these drugs may have benefits as part of prophylactic regimens designed to prevent infection.…”
Section: Discussionmentioning
confidence: 99%
“…New treatments designed to disrupt the function of Nef and Vpu will likely aid host immunity combat HIV-1 infection by restoring normal PM physiology. In fact, Nef and Vpu antagonists are currently in development [ 176 , 177 ]. Given the ability of Nef and Vpu to overcome intrinsic restriction factors and innate immunity, these drugs may have benefits as part of prophylactic regimens designed to prevent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Vpu proteins expressed by several of these viruses were unable to oppose tetherin, suggesting that this function may be acquired by Nef under circumstances where it is lost by Vpu. One implication of these observations is that efforts to develop antiretroviral drugs that interfere with the ability of Vpu to counteract tetherin may lead to the selection of Nef variants that gain this function (57,58). Thus, understanding the conditions that lead to tetherin antagonism by Nef will be important for the development of therapies to increase the susceptibility of HIV-1 to this restriction factor.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 227 developed a cell-based high-throughput enzyme-linked immunosorbent assay for the quantification of cell-surface BST-2 levels, 227 and a lead compound IMB-LA (95; Figure 19) was identified to inhibit Vpu-mediated BST-2 degradation and recover the expression of BST-2 at the cell surface. 228 This compound inhibited both the HIV infection and release in a BST-2 dependent fashion. The mechanism studies showed that compound 95 did not inhibit the interaction between BST-2 and Vpu, but it blocked the sorting of BST-2 into JI AND LI | 23 lysosomes for degradation.…”
Section: Bone Marrow Stromal Cell Antigenmentioning
confidence: 97%